2013
DOI: 10.1055/s-0033-1357185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin Supplementation on Exercise-Induced Oxidative Stress in Humans

Abstract: The purpose of this study was to investigate the effects of curcumin supplementation on exercise-induced oxidative stress in humans. 10 male participants, ages 26.8±2.0 years (mean±SE), completed 3 trials in a random order: (1) placebo (control), (2) single (only before exercise) and (3) double (before and immediately after exercise) curcumin supplementation trials. Each participant received oral administration of 90 mg of curcumin or the placebo 2h before exercise and immediately after exercise. Each particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 17 publications
4
92
0
2
Order By: Relevance
“…We demonstrated that neutrophils firstly migrate to the damaged muscle, attract macrophages, and induce inflammatory mediators and cytokines [12]. Although curcumin is known to protect against ischemia/reperfusion injury in rat skeletal muscle [22], we demonstrated exercise-induced oxidative stress was attenuated by prior curcumin ingestion in vivo in humans [23]. Taheebo extract includes polyphenols that were found to suppress not only oxidative stress, but also the production of inflammatory cytokines and prostaglandin E2 by blocking cyclooxygenase-2 (COX-2) in the same manner as anti- …”
Section: Related and Supplementary Findingsmentioning
confidence: 84%
“…We demonstrated that neutrophils firstly migrate to the damaged muscle, attract macrophages, and induce inflammatory mediators and cytokines [12]. Although curcumin is known to protect against ischemia/reperfusion injury in rat skeletal muscle [22], we demonstrated exercise-induced oxidative stress was attenuated by prior curcumin ingestion in vivo in humans [23]. Taheebo extract includes polyphenols that were found to suppress not only oxidative stress, but also the production of inflammatory cytokines and prostaglandin E2 by blocking cyclooxygenase-2 (COX-2) in the same manner as anti- …”
Section: Related and Supplementary Findingsmentioning
confidence: 84%
“…The levels of these enzymes improved after chronic Ex and antioxidant supplementation (grape seed extract). Takahashi et al27 reported that the serum biological antioxidant potential concentrations after Ex were much higher in single and double CW supplementation trials compared to those before Ex. CW supplementation can attenuate Ex-induced oxidative stress and increase blood’s antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant underwent 2 laboratory-based trials in randomized order: (1) placebo (control), (2) between trials. Curcumin was provided by the Thera values Corporation design (Tokyo, Japan) (26). The product was developed to result in much higher plasma concentration and bioavailability after intake compared to conventional curcumin powder.…”
Section: Methodsmentioning
confidence: 99%